Insomnia. Issue 10357 (24th September 2022) - Perlis, Michael L; Posner, Donn; Riemann, Dieter; Bastien, Celyne H; Teel, Joseph; Thase, Michael
Abstract : Insomnia is highly prevalent in clinical practice, occurring in up to 50% of primary care patients. Insomnia can present independently or alongside other medical conditions or mental health disorders and is a risk factor for the development and exacerbation of these other disorders if not treated. In 2016, the American College of Physicians recommended that insomnia be specifically targeted for treatment. The recommended first-line treatment for insomnia, whether the underlying cause has been identified or not, is cognitive behavioural therapy for insomnia (CBT-I). Currently, there is no global consensus regarding which pharmacological treatment has the best efficacy or risk-benefit ratio. Both CBT-I and pharmacological intervention are thought to have similar acute effects, but only CBT-I has shown durable long-term effects after treatment discontinuation. Administering a combined treatment of CBT-I and medication could decrease the latency to treatment response, but might diminish the durability of the positive treatment effects of CBT-I.